Partial Replacement of Cement Concreete with Biological Green Waste - Vamshi Krishna, Tolmatti; Ashwin Kumar, M.; Anjaneyulu, Kunchala (International Journal of Engineering and Technology, 2018)
Bagasse ash (BA), the residue obtained after the burning of sugarcane bagasse as a fuel, has pozzolanic properties with potential use as a supplementary binding material (SCM). Use of Bagasse ash (BA) as a mineral admixture needs to be established, especially in India, where sugarcane cultivation is widespread, to reduce land required for its disposal and cement consumption in construction industry. Hence, to encourage commercial use ofBA with minimum processing, an evaluation of the physical, chemical andÂ morphological characteristics of a locally available BA and its effect, as SCM on properties of structural concrete was taken up.This research work describes the feasibility of using the Fly Ash (FA) Rice Husk Ash (RHA) and Sugarcane Bagasse Ash(SCBA) waste in concrete production as a partial replacement of cement. This present work deals with the effect on strength and mechanical properties of concrete using Triple blending of cement concrete using FA, RHA and SCBA instead of cement. The cement has been replaced by rice husk ash, accordingly in the range with 0%, 10%, 20% and 30% by weight. Concrete mixture of M20 and M25 and M30, were produced, tested and compared in terms of compressive strengths with the Conventional concrete. These tests were carried out to evaluate the mechanical properties for the test results of7, 14, 28, 56 and 90 days for Compressive strengths and Tensile & Flexural Strengths at 28 days. The durability aspect of the samples for Acid attack, Alkaline attack and Sulphate attack was also tested. The result indicates that the FA, RHA and SCBA improve the Compressive Strength and durability of concrete.Â Â